Fire performance of cultural heritage and contemporary timbers. (15th December 2019) - Chorlton, Bronwyn; Gales, John
Highlights: Historic timber performs significantly different to contemporary timber in fire. Representative samples from real historic buildings were compared to modern samples with controlled and repeatable fire tests. Needed heritage preservation techniques with respect to fire safety. Historic timber did not perform as well as the contemporary samples with respect to char depth, time to ignition, and flame spread, with a difference in char rate of up to 20%. Abstract: Cultural heritage buildings are important reminders of our history, and timber is one of the materials commonly found within these structures. While cultural heritage buildings often hold significant aesthetic, historic, or cultural value, they are also frequently vulnerable to fire. In order to improve the fire performance of these buildings, the timber elements are often removed or covered by another material. When these alterations are done, the heritage value of the building is obscured. On the other hand, increasingly larger and taller timber buildings are being constructed out of contemporary/engineered timber, and fire safety engineering strategies have been found to justify the adequate fire performance of these contemporary structures. This manuscript herein addresses if historic timber performs significantly different to contemporary timber in fire. Controlled and repeatable fire tests have been performed on four different types of timber, two contemporary Glued Laminated Timbers (Glulam) and two historic timbers from buildings constructed in 1898 and 1839. The timber was tested using Lateral Ignition and Flame Spread Test and Cone Calorimeter apparatuses, following ASTM E1321 and ASTM E1354 standards, to compare the relative performance of the timber types in their char depth, time to ignition, and flame spread. Results showed that the historic timber did not perform as well as the Glulam in the aforementioned categories, with the historic timber charring at a rate up to 20% faster. This study is novel by providing an indication of the fire performance of timber that was used hundreds of years ago, by comparing it to timber used today. Successful heritage conservation efforts in leaving the timber exposed and in-place become possible once the performance of the timber is understood, and other fire safety engineering strategies (respectful of the heritage structure) are in place.